Effects of elagolix on the pharmacokinetics of omeprazole and its metabolites in healthy premenopausal women - Ahmed Nader; Nael M. Mostafa; Elaine Kim; Mohamad Shebley (Clinical and Translational Science, 2022)
Abstract This study evaluated the effect of repeated doses of elagolix on the pharmacokinetics (PK) of omeprazole and its metabolites in healthy premenopausal female subjects. Adult premenopausal female subjects (N = 20) received a single oral dose of omeprazole (40 mg) on day 1 and day 11 and oral doses of elagolix (300 mg) twice‐daily on days 3–11. Serial blood samples for assay of omeprazole and its metabolites were collected for 24 h after dosing on days 1 and 11. PK parameters were calculated for omeprazole, 5‐hydroxyomeprazole and omeprazole sulfone; and were compared between day 1 and day 11. Pharmacogenetic testing was performed for CYP2C19 variant alleles and the results were used to compare the magnitude of elagolix–omeprazole drug–drug interaction (DDI) between the different genotype subgroups. Administration of elagolix 300 mg twice‐daily for 9 days increased omeprazole exposure by 1.8‐fold and decreased the metabolite‐to‐parent ratio for 5‐hydroxyomeprazole by ~60%. Conversely, there was an increase in the metabolite‐to‐parent ratio for omeprazole sulfone by 25%. Elagolix increased omeprazole exposures by 2‐ to 2.5‐fold in CYP2C19 extensive (EM) and intermediate (IM) metabolizer subjects, but decreased omeprazole exposures by 40% in poor metabolizer subjects. Exposures of 5‐hydroxyomeprazole decreased by 20%–30% in all genotype subgroups, and omeprazole sulfone exposures increased by ~3‐fold in EM and IM subjects. Elagolix is a weak inhibitor of CYP2C19 and exposure of CYP2C19 substrates may be increased upon coadministration with elagolix. Omeprazole may exhibit drug interactions due to multiple mechanisms other than CYP2C19‐mediated metabolism; complicating the interpretation of results from omeprazole DDI studies.